Social Disadvantage and Instability in Older Adults' Ties to Their Adult Children. Issue 5 (19th June 2018) - Goldman, Alyssa W.; Cornwell, Benjamin
Abstract : Objective: The authors examine whether racial and socioeconomic factors influence older adults' likelihood of experiencing instability in their social network ties with their adult children. Background: Recent work shows that socially disadvantaged older adults' social networks are more unstable and exhibit higher rates of turnover, perhaps due to greater exposure to broader social–environmental instability. The authors consider whether this network instability applies to older adults' ties with their adult children, which are often among the closest and most valued social ties in later life. Methods: The authors use two waves of data from the National Social Life, Health, and Aging Project (N = 1, 456), a nationally representative, longitudinal study of older Americans. Through a series of multivariate regression models, the authors examine how race and education are associated with how frequently older adults reported being in contact with child network members, and how likely older adults were to stop naming their children as network members over time. Results: African American and less educated individuals reported significantly more frequent contact with their adult child network members than did Whites and more educated individuals. Nevertheless, African American and less educated older adults were also more likely to stop naming their children as network confidants over time. Conclusion: African American and less educated older adults may be at greater risk of losing access to the supports and other resources that are often provided by adult children, or of not being able to consistently draw on them as they age, despite the fact that these ties demonstrate greater potential for support exchange at baseline.